Online and Offline Contributions in Adapted Movements - Wijeyaratnam, Darrin (Université d'Ottawa / University of Ottawa, 2018)
Human movements are remarkably adaptive, such that we are capable of completing movements in a novel environment with similar accuracy to those performed in a typical environment. Our ability to perform in these environments involves accurate processing of sensory feedback for online and offline control. These processes of control have been widely studied for well learned actions, but not for actions in a novel visuomotor environment. In two experiments, we examined control processes underlying reaches when participants were first introduced to a visuomotor rotation (Experiment 1) and then following visuomotor adaptation (Experiment 2). All participants completed 150 reach training trials when (1) a cursor accurately represented their hand motion (i.e., aligned cursor) and (2) a cursor was rotated 45 degrees clockwise relative to their hand motion (i.e., rotated cursor). In Experiment 1, we sought to determine if the control processes underlying movements in typical and novel visuomotor conditions were comparable. Participants (n = 16) received either continuous visual feedback or terminal visual feedback regarding movement endpoint during reach training. Analyses revealed that participants were able to demonstrate similar outcomes (i.e., movement time and endpoint errors) regardless of visual or cursor feedback, but also demonstrated more offline control (i.e., took more time planning and were less consistent in initiating their movements) when reaching with a rotated cursor compared to an aligned cursor, even at the end of training. Together, the results suggest a greater contribution of offline control processes and less effective online corrective processes when reaching in a novel environment compared to when reaching in a typical environment. In attempt to promote online corrective processes, participants (n = 16) in Experiment 2 first completed the training trials with continuous visual feedback and then completed an additional 45 reaches under (1) slow movement time (i.e., Slow MT: 800-1000 ms) and (2) fast movement time (i.e., Fast MT: 400-500ms) constraints. Results showed a shift to online control (i.e., greater endpoint accuracy) when reaching with an aligned and rotated cursor, when sufficiently more time was provided (i.e., Slow MT). Specifically, participants were able to more effectively utilize visual feedback for online control under the Slow MT constraint compared to when reaching quickly (i.e., Fast MT). Together, these experiments demonstrate a flexibility in control processes underlying reaches with rotated visual feedback of the hand. In that reaches first engage in offline control processes during adaptation to a visuomotor rotation, and then shift to online corrective processes following visuomotor adaptation.
Keywords: Reaching; Visuomotor adaptation; Visual feedback; Kinematic analysis; Movement control; Online control; Offline control; Speed-accuracy trade-off